Diagnostic Musculoskeletal Ultrasound for Medial Collateral Ligament Injuries: Applications in Rehabilitation - Robert C. Manske; Michael Voight; Chris Wolfe; Phil Page (International Journal of Sports Physical Therapy)
Medial collateral ligament (MCL) injuries are prevalent in sports and other physical activities and constitute a significant cause of knee pain and dysfunction. Traditional diagnostic modalities such as magnetic resonance imaging (MRI) are often utilized for their detailed visualization capabilities. However, musculoskeletal ultrasound (MSK-US) has emerged as a pivotal diagnostic tool in the evaluation of MCL injuries due to its non-invasive nature, cost-effectiveness, and dynamic imaging capabilities. This article reviews the utility and advantages of MSK-US in diagnosing MCL injuries, with a specific focus on its implications for rehabilitation providers. We discuss the technical aspects of ultrasound (US) imaging, including the sonographic appearance of MCL injuries across various grades, and compare its diagnostic accuracy with other imaging modalities such as MRI. Additionally, the role of US in monitoring the healing process and guiding rehabilitation strategies is explored. This review emphasizes the practical application of MSK-US in clinical settings, offering rehabilitation providers a comprehensive understanding of how US can be integrated into patient management protocols to enhance outcomes in patients with MCL injuries.